Analysis of Phonological Errors in SD N 1 Jojo on The Theme of Heroes - Kiswanti; Syarifah Nur Aulia; Mefiani, Sandrina; Rani Setiawaty (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to describe errors in language use, especially in the area of phonology, in students' essays at SD N 1 Jojo. The method used in this research is qualitative narrative. The data comes from a narrative essay entitled "Analysis of Phonological Errors in Elementary School N 1 Jojo Students' Essays with the theme of heroes" written by fourth grade students at SD N 1 Jojo. Data collection techniques are obtained using documentation techniques which are obtained by documenting student essays. Data analysis uses analytical techniques with the Miles and Huberman model, which is interactive and continues until completion. The results of the research showed that there were 30% phonological errors in the essays of SD N 1 Jojo students with the theme of heroes. The phonological errors that we analyze include errors in using capital letters in the first letters of holidays 5%, errors in writing compositions of words in sentences 5%, errors in spelling words in sentences 5%, errors in using inappropriate prepositions 5%, errors in using inappropriate conjunctions 5%, and discrepancy in the pronunciation of sounds 5%.